Being Mindful at University: A Pilot Evaluation of the Feasibility of an Online Mindfulness-Based Mental Health Support Program for Students - Světlák, Miroslav; Linhartová, Pavla; Knejzlíková, Terezia; Knejzlík, Jakub; Kóša, Barbora; Horníčková, Veronika; Jarolínová, Kristýna; Lučanská, Klaudia; Slezáčková, Alena; Šumec, Rastislav (Frontiers in Psychology, 2021)
University study can be a life period of heightened psychological distress for many students. The development of new preventive and intervention programs to support well-being in university students is a fundamental challenge for mental health professionals. We designed an eight-week online mindfulness-based program (eMBP) combining a face-to-face approach, text, audio, video components, and support psychotherapy principles with a unique intensive reminder system using the Facebook Messenger and Slack applications in two separate runs (N = 692). We assessed the program’s effect on mindful experiencing, perceived stress, emotion regulation strategies, self-compassion, negative affect, and quality of life. The results of the presented pilot study confirmed that eMBP is a feasible and effective tool in university students’ mental health support. The students who completed the eMBP reported a reduction of perceived stress with large effect size (pη2 = 0.42), as well as a decrease of negative affect experience frequency and intensity (pη2 = 0.31), an increase of being mindful in their life (FFMQ subscales: pη2 = 0.21, 0.27, 0.25, 0.28, 0.28), and a higher rate of self-compassion (pη2 = 0.28) with a medium effect size. A small effect size was found in the frequency of using a cognitive reappraisal strategy (pη2 = 0.073). One new result is the observation of an eMBP effect (pη2 = 0.27) on the decrease in attributed importance to the quality of life components replicated in two consecutive runs of the program. The study affirms that mindfulness-based interventions can be effectively delivered in an eHealth form to university students.